GATA1 mutation negative acute megakaryoblastic leukemia with acquired trisomy 21 presenting with extensive bone marrow necrosis in an adult: A case report and review of the literature - Todd P. Williams; Richard D. Hammer, MD (Elsevier, 2016)
Context: Acute megakaryoblastic leukemia (AMKL) is a rare myeloid leukemia, occurring in 1%-5% of all adult acute myeloid leukemia (AML) cases. AMKL is characterized by a leukemic blast population positive for factor VIII, CD41a, CD42b, and/or CD61 with extensive myelofibrosis. Although various cytogenetic abnormalities are commonly reported, the association between constitutional trisomy 21 and AMKL has been of particular interest, because of the near universal presence of GATA1 mutation in such cases. Objective and Design: We report a case of AMKL in an adult presenting with extensive bone marrow necrosis in which cytogenetic studies revealed three copies of chromosome 21 as part of a complex karyotype; however, sequencing of the GATA1 gene revealed no mutation. Results: The patient was an adult male who presented with extensive bone marrow necrosis, making definitive diagnosis difficult. Autopsy studies using a multimodality approach identified AMKL with a complex karyotype, including trisomy 21. Sanger sequencing of the GATA1 gene showed a germline configuration without a mutation. Conclusions: To our knowledge, this is the first reported case of an adult with AMKL with acquired trisomy 21 in which the GATA1 mutation was investigated and the second reported case of AMKL presenting with extensive bone marrow necrosis. We will present a diagnostic approach to AMKL in which extensive bone marrow necrosis renders examination of the bone marrow difficult. Furthermore, we will examine the absence of the GATA1 mutation in a case of AMKL with trisomy 21 in an adult.